2011
DOI: 10.1007/s11102-011-0366-4
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tumor-derived ectopic hyperprolactinemia

Abstract: To describe extreme hyperprolactinemia originating from a pituitary adenoma in the wall of an ovarian dermoid. This is a description of an unusual case and a review of ectopic prolactin production. Ectopic production of prolactin is a rare condition that has been reported in isolated organ system pathology including ovaries. An ovarian dermoid is a benign neoplasm that has the potential for active unregulated endocrine function. Hyperprolactinemia can result from functioning lactotrophs found in ovarian dermoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The predominant form in healthy subjects and in patients with prolactinomas is monomeric PRL (molecular mass 23 kDa), while dimeric or big PRL (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and big-big PRL or macroprolactin (150-170 kDa) correspond to less than 20% of the total PRL (13)(14)(15). When the serum of a patient with hyperprolactinemia contains mostly macroprolactin, the condition is termed macroprolactinemia (16,17).…”
Section: Prolactin Serum Isoformsmentioning
confidence: 99%
“…The predominant form in healthy subjects and in patients with prolactinomas is monomeric PRL (molecular mass 23 kDa), while dimeric or big PRL (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and big-big PRL or macroprolactin (150-170 kDa) correspond to less than 20% of the total PRL (13)(14)(15). When the serum of a patient with hyperprolactinemia contains mostly macroprolactin, the condition is termed macroprolactinemia (16,17).…”
Section: Prolactin Serum Isoformsmentioning
confidence: 99%
“…According to the literature [1], the detection of ectopic pituitary tissue within a mature ovarian teratoma is exceedingly rare and different kinds of pituitary cells could be found [2]. In our patient there was hyperplasia of PRL+ cells in the presence of normal hormone levels and in the absence of clinical endocrine dysfunction.…”
Section: Discussionmentioning
confidence: 49%
“…Elms et al [2] described a 1.5 Â 1.0 cm ectopic active pituitary neoplasm producing PRL within a dermoid cyst. Moreover, Al-Bazzaz et al [3] reported ectopic adenohypophyseal tissue in a dermoid cyst with predominant PRL-immunopositive cells and also GH and ACTHimmunopositive cells.…”
Section: Discussionmentioning
confidence: 99%
“…In non-pathological states, prolactin secretion has been demonstrated in decidua, mammary tissue, ovaries, the male reproductive tract, epithelial cells, the immune system, brain, hair follicles, and skin [3]. Extra-pituitary pathological prolactin secretion has been described from perivascular epithelioid tumors [4,5], ovarian tumors [6][7][8], acute lymphoblastic and myeloid leukemias [9][10][11], colorectal adenocarcinoma [12,13], non-Hodgkin's lymphoma [14], renal cell carcinoma [15], renal epitheloid angiomyolipoma [16], cervical cancer [17], and lung cancer [18].…”
Section: Discussionmentioning
confidence: 99%